2011
DOI: 10.1097/mop.0b013e3283423e51
|View full text |Cite
|
Sign up to set email alerts
|

Future applications of antioxidants in premature infants

Abstract: Purpose of Review This review will examine the unique susceptibility of premature infants to oxidative stress, the role of reactive oxygen species (ROS) in the pathogenesis of common disorders of the preterm infant, and potential for therapeutic interventions using enzymatic and/or non-enzymatic antioxidants. Recent Findings Oxidative stress is caused by an imbalance between the production of ROS and the ability to detoxify them with the help of antioxidants. The premature infant is especially susceptible to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
89
0
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(97 citation statements)
references
References 44 publications
1
89
0
7
Order By: Relevance
“…This finding is in perfect accordance with the previous data published by other investigators (23)(24)(25)(26)(27), and could be explained by the inadequate supply of specific cofactors, essential for the proper functioning of these enzymes: copper, zinc and selenium, respectively; since placental maternal-to-fetal passage is very limited before (the latter part of) the third trimester (28). Production and activity of antioxidant enzymes increase markedly in the final days before birth, and even more so after birth (29). Therefore, premature birth could itself be considered an illness with a major oxidative component.…”
Section: Discussionsupporting
confidence: 78%
“…This finding is in perfect accordance with the previous data published by other investigators (23)(24)(25)(26)(27), and could be explained by the inadequate supply of specific cofactors, essential for the proper functioning of these enzymes: copper, zinc and selenium, respectively; since placental maternal-to-fetal passage is very limited before (the latter part of) the third trimester (28). Production and activity of antioxidant enzymes increase markedly in the final days before birth, and even more so after birth (29). Therefore, premature birth could itself be considered an illness with a major oxidative component.…”
Section: Discussionsupporting
confidence: 78%
“…Markers of oxidative stress are often overexpressed in the airways in several chronic lung disorders, and they are linked to ongoing airway inflammation and remodelling [12]. Oxidative stress has also been consistently associated with lung injury early in life, in infants who progress towards BPD [13], and there is increasing evidence to link early exposure to oxidative stress with potentially lifelong consequences [14]. Oxygen radicals have many complex effects on the body's homeostasis, being involved in normal organ development and contributing to several physiological functions [13].…”
mentioning
confidence: 99%
“…In addition to these agents, antioxidants are believed to represent a promising treatment option, not only for preterm birth (7,14,24) but also for neonatal disorders, bronchopulmonary dysplasia, retinopathy of prematurity, necrotizing enterocolitis, and periventricular leukomalacia (25). We showed that TRX is one of the potential agents for intrauterine infection/inflammation by its antioxidant and anti-inflammatory properties.…”
Section: Discussionmentioning
confidence: 93%